Jatropha curcas L. as potential bio-coagulant for wastewater treatment - Madehi, Norhafiza (2013)
This project aims to investigate the potential use of Jatropha Curcas (JC) as a bio-coagulant in wastewater treatment. The first objective of this study was to investigate the performance of JC for its potential use as a bio-coagulant compared to alum. Palm Oil Mill Effluent (POME) is wastewater generated from the palm oil milling industry. It is a highly polluted wastewater which contains high Chemical Oxygen Demand (COD), typically averaging from 30,000 to 43,700 mg/L, with Biological Oxygen Demand (BOD), from 20,000 to 30,000 mg/L and Total Suspended Solids (TSS) from 18,000 to 18,500 mg/L. It is acidic in pH ranging from pH 4.6 to 4.8 and brownish in colour. When freshly discharged, POME has a temperature of between 80 and 90oC. POME consists of a high volume of liquid waste which is non-toxic but has an unpleasant odour, and must be treated properly before being discharged into the environment. The use of inorganic coagulants like alum has led to the spread of chronic diseases due to the residual content of the coagulants in the treated wastewater. Thus, this study searched for an alternative using JC plant, a bio-resource. Coagulation and flocculation methods were used in this study. In this study, the optimum condition for synthetic water kaolin treatment was at pH 2, with a dosage of 120 mg/L, and with 99% turbidity removal. It was found that JC presscake showed better coagulation performance compared to JC seed coagulant, with 99% turbidity removal at an optimum pH of 3 and 140 mg/L dosage concentration. JC seeds, on the other hands,showed the potential to remove about 93% turbidity at the optimum of pH of 3 and with 120 mg/L dosage. Furthermore, the performance of JC as a bio-coagulant was compared to aluminum sulphate (alum) coagulant. The results showed that alum gave 93% turbidity removal at optimum pH 5 and with an optimum dosage of 1200mg/L. The treatment of POME wastewater by using JC presscake as a bio-coagulant was successfully able to reduce COD with up to 70% in value, 65% of BOD reduction and 88% of TSS removal, whereas alum coagulant resulted in 59% of COD, 61% of BOD reduction and 71% of TSS removal. The second objective of this study was to examine the characterization of the composition of JC seed and JC presscake as potential coagulant agents for wastewater treatment by using High Performances Liquid Chromatography (HPLC) analysis. The results showed that 18 types of amino acid were detected. The amino acid Lysine was detected to have the highest composition in JC seed with 24.87%, followed by the amino acid, Cystine, with 21.74% in composition. JC presscake, on the other hand, had the highest composition for the amino acid Phenylalanine with 15.34%, followed by the amino acid Cystine with 14.21%. For the third objective of this study, a final quantitative analysis through HPLC was conducted. The final treated POME was run through HPLC analysis to detect the presence of Phorbol-esters. The peaks indicated that there was no Phorbol-ester in the treated wastewater solution. As a conclusion, this study has proven that JC presscake has a high potential to be used as a bio-coagulant for wastewater treatment. The estimated cost for treatment using JC seed was RM 0.035 per 1 liter of wastewater treated. JC presscake coagulant is cheaper than JC seed kernel coagulant if JC presscake coagulant can be directly obtained from the industry’s extraction process of Jatropha oil.